Résurrection numérique, deuil et données personnelles : décryptage des imaginaires dystopiques et des enjeux éthiques de l’IA dans l’épisode « Be Right Back » de Black Mirror - Marine Malet (Belphégor)
Directed by Owen Harris and broadcast on Channel 4, the Black Mirror episode “Be Right Back” (S02E01) features an artificial intelligence programmed to enable conversations with deceased people. Considering contemporary TV series are likely to be involved in framing public issues, this article investigate how AI is portrayed and the risks associated with it by using the dystopian genre. Combining an episode analysis and a reception study, it aims to ask whether fiction offers a simple dystopian anticipation or whether its collective discussion suggests the development of a critical and reflexive stance towards our contemporary societies and current issues linked to AI, thus contributing to the collective debate.